Analisis Daya Dukung Dan Daya Tampung Di Tinjau Dari Aspek Ruang Pertanian - Siti Nur Rofi'ah; Boby Rahman (Jurnal Ilmiah Penelitian Mahasiswa, 2023)
Recently, the carrying capacity and carrying capacity of the environment (DDDTL) are currently being discussed. The high population growth which results in the development rate greatly influences environmental sustainability. Increased population growth causes the need for space for built-in land such as housing to also increase. Of course, once the land is built, it will be accompanied by an increase in natural resource needs such as air. DDDTL is an alarm to wake up whether the resource capacity is available or not to support the large number of people in an area. This is at the same time to measure the limits of the existing space to keep it under control. The qualitative analysis method with the literature review approach was chosen to examine in this study. There are several factors that can influence or not DDDT for agricultural land in an area. DDDT agricultural land that is developed by the area of harvested land, population, food production and minimum physical consumption. Meanwhile, water DDDT is influenced by the average rainfall, population, water needs per person, and area. Keywords: DDDTL, DDDT Agricultural Land and DDDT Water